NOVEL ANALYZING APPROACHES FOR CHEMICAL CHARACTERIZATION OF SUNFLOWER OILS DURING DEEP-FRYING BY FT-IR - Karaogul, Eyyup; Al, Sumeyra; Karakus, M. Sukru; Atasoy, A. Ferit; Alma, M. Hakki (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2020)
The main aim of this study is to investigate the change in the chemical properties on frying cycles of Sunflower oil by FT-IR. Deep-frying (DFO) was carried out 9 times for 20 minutes. The main characteristic bands in the FT-IR spectra were determined to be concerned to peroxide, cis, trans, -CH3, -CH2, ester and ether groups. Additionally, the index calculations and formulation from FT-IR spectra were applied and this technique was novel for characterization of the oil about interactions between virgin oil (VO) and DFO. Depending on the index calculations, Cis Index (Cs-Inx), trans index (Trs-Inx), ester index (Est-Inx), methyl index (Mt-Inx), peroxide index (Prx-Inx), ether index (Et-Inx) and unsaturated oil index (Ust-Inx) were investigated. Results demonstrated that Cs-Inx, Est-Inx and Ust-Inx were decreased with the frying process unlike Trs-Inx, Mt-Inx, Prx-Inx and Et-Inx because of oil's degradations. In addition, the 1st, 2nd, 3rd, and 4th FT-IR derivatives were also displayed better interpretation of the interactions between VO and DFO. It was concluded that FT-IR spectra and derivatives could be used as a new perspective to investigate the chemical properties of oils and index calculations.
Keywords: Oil; Deep -Frying; FT-IR; Index; Derivative; VIRGIN OLIVE OILS; SPECTROSCOPY; AUTHENTICATION; DOLOMITE; TUBER; FATS; Environmental Sciences & Ecology